Spectrophotometric Evaluation of the Behavior of Disperse Red 1 Dye in Aqueous Media and its Interaction with Calf Thymus ds-DNA - Uliana, Carolina V. [UNESP]; Garbellini, Gustavo S. [UNESP]; Yamanaka, Hideko [UNESP] (Soc Brasileira Quimica, 2012)
UV-Vis spectrophotometry was used to measure the solubility of disperse red 1 (DR1) dye in aqueous solutions, using different solvents and dispersants. The dye was quantified in water samples, and its interaction with calf thymus ds-DNA was investigated. The results showed that the commercial dispersant Fongranal (R) FB was suitable for the preparation of aqueous DR1 solutions. For the determination of DR1 in purified water, the limit of detection was 2.47 x 10(-6) mol L-1, and the limit of quantification was 8.22 x 10(-6) mol L-1. Percentage recoveries of 91.2 and 103% were obtained for DR1 concentrations of 3.00 x 10(-6) and 40.0 x 10(-6) mol L-1, respectively. The recoveries achieved for DR1 present in tap and river water were in the range 85.9-113%. The interaction of DR1 with calf thymus DNA was accompanied by hypochromic and hyperchromic effects, which were related to conformational changes and damage to the DNA double helix.
Keywords: disperse red 1; textile dye; solubility; ds-DNA